“I HATE ENGLISH BUT I CAN BEAT IT” A LOOK AT ISLAMIC STUDENT’S STRATEGY IN LEARNING ENGLISH - Durratul Hikmah; Nurmala Nurmala; Nurhayati Nurhayati (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study explores the personal journey of an Indonesia student, pseudonymously named Arka, as he developed English-speaking competence through a combination of environmental immersion, emotional resilience, and strategic learning behaviors. Using a narrative inquiry approach and grounded in Oxfords (1990) language learning strategy framework, this research highlights how Arka evolved from a disinterested English learner in junior high school to a confident, fluent speaker and top graduate in English Education. Data were collected through in-depth interviews, observations, document analysis, and peer verification to ensure validity. The findings reveal that Arkas language development was shaped by a dynamic use of direct and indirect learning strategies, including memory, cognitive, compensation, metacognitive, affective, and social strategies. his experience underscores the critical role of learning environments, personal motivation, and emotional regulation in mastering English-speaking skills. This research offers practical insights for language teachers, learners, and researchers by demonstrating how individual experiences and self-directed strategy use can bridge the gap between classroom instruction and real-world communicative competence.